Pelatihan Manajemen Koperasi PKK RW.04 Kelurahan Timur Indah Kacamatan Singaran Pati Kota Bengkulu - Kasdi, By; Setyani , Sindy Ambar (Jurnal Kewirausahaan dan Bisnis, 2021)
The PKK RW.04 Cooperative Management Training in Kelurahan Timur Indah, Kecamatan Singaran Pati, Bengkulu City, aimed to improve the management capacity of cooperatives at the rural level. The study identified various aspects of cooperative management that require special attention, including financial management, leadership, innovation, and marketing strategies. The training methods used included material delivery, interactive discussions, and case studies to provide a comprehensive understanding of effective cooperative management practices. The training evaluation showed an increase in participants' knowledge and skills in cooperative management, as well as its positive impact on the performance of the PKK RW.04 cooperative. The implication of this study is the importance of structured and sustainable management training in supporting cooperative development at the local level, so as to improve members' welfare and the cooperative's contribution to local economic development.